PRODUCT PERFORMANCE ASSESSMENT IN 2013 CURRICULUM FOR ELEMENTARY SCHOOL STUDENTS - Haryanti, Yuyun Dwi (Universitas Sebelas Maret, 2018)
Assessment on the 2013 Curriculum focuses on performance assessment. Performance assessment as a broad-range assessment of student activity in which students are not only able to complete sentences, write essays but conduct research, investigations, analyze situations and data, to communicate and collaborate. Therefore, the students real performance to build performance naturally and at the same time develop thinking, reasoning, intellectual, and self-mating skills. Assessment of the product as a basis for student assessment because it requires students to apply the initial knowledge to solve problems that are realistic experienced students. Students solve various problems encountered and then expressed through the explanation he made either in the form of writing, pictures, or other products. The development of the century is characterized by increasingly fierce competition in both the business world and the world of work. Appropriate, the process of learning, especially at the elementary school equip students development entrepreneurial spirit and have life skills.